DOES ALTITUDE AND FOREST DENSITY AFFECT ECONOMIC GROWTH? A CASE STUDY OF KALIMANTAN BARAT - Islahiyah, Djihan; Vikki, Vikki (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2021)
Kalimantan Barat is one of the individual provinces in Kalimantan due to its diverse geographical elevation among all districts. Mountains and hills dominate the districts near the border; lowlands and river banks dominate the urban areas. A geographical indication is a barrier to economic growth, as a simple growth from limited transportation. Efforts to optimize the economic sector are also carried out in forest management, including Kalimantan Barat as one of the world's lungs. The conversion of forest land functions is suspected to increase economic growth even though it must balance nature. This study aims to determine the significance of altitude as a fixed geographical indicator and forest density as a natural condition that can vary according to human activities. The height of area data and forest density, and the average economic growth in 14 districts/cities in Kalimantan Barat uses the Panel Least Square method. As a result, area height has a negative and significant effect on economic growth, whereas forest density has no such relationship. Simultaneously, both variable is having a substantial impact on economic growth in Kalimantan Barat.